Factors affecting lymphedema after neoadjuvant chemotherapy and axillary dissection in female breast cancer patients: a retrospective cohort study based on the Chinese population - Fu, Jianqin; Chen, Ruiliang; He, Lijuan; Bao, Liqun; Lin, Zhaodi; Jiang, Weijing; Zhang, Jie; Wang, Chuan; Lin, Yanjuan (Frontiers in Oncology, 2024)
PurposeBreast cancer-related lymphedema (BCRL) is a common complication among breast cancer survivors. Most BCRL studies have focused on patients receiving adjuvant chemotherapy, with relatively little attention paid to BCRL in patients undergoing neoadjuvant chemotherapy (NAC). This study aimed to investigate the risk factors associated with BCRL in Chinese women undergoing NAC and axillary lymph node dissection (ALND).MethodsAt our institution, this cohort study collected data from 336 women with breast cancer and documented axillary nodal metastasis at diagnosis, who received NAC and ALND surgery between 2015 and 2020. BCRL was assessed through both objective limb circumference measurements and subjective self-reported symptoms. Multivariate logistic regression was employed to identify risk factors for BCRL, considering clinical, demographic, and lifestyle-related characteristics.ResultsThe cumulative incidence of BCRL within 2.5 years was 43.75%. Factors independently associated with BCRL included radiotherapy (versus no radiotherapy; hazard ratio (HR) = 1.611; P = 0.020), NAC duration of 105 days or shorter (versus 105-143 days; HR = 0.471; P = 0.020), removal of more than 15 lymph nodes (versus 15 or fewer lymph nodes; HR = 1.593; P = 0.036), drainage duration of 20-29 days (versus 10-19 days; HR = 1.568; P = 0.028), and sleeping biased toward the affected arm (versus sleeping biased toward the healthy arm; HR = 2.033; P = 0.019).ConclusionThis study identified several risk factors for BCRL in breast cancer patients following NAC and ALND. Patients presenting with one or more of these factors should be monitored closely for early detection and intervention. Further research is warranted to explore the impact of drainage duration and sleep position on the development of BCRL.